Penetapan Kadar HMF dalam Madu Menggunakan Kromatografi Kinerja Tingkat Tinggi - Dimyati, Erin; Marzuki, Hasan (Jurnal Multidisipliner Bharasumba, 2023)
The circulation of counterfeit honey educates the public about the authenticity of honey by informing them about the honey content, including Hydroxymethyl Furfural (HMF), which indicates the purity of honey. The sample for this study was packaged honey circulating in the community, and the HMF levels were determined using an HPLC instrument. With the results of this study, there was 1 sample of honey containing an HMF level of 295.58 mg/kg, so the level value exceeded the safe limit for consumption according to the 2019 BPOM regulations of 50 mg/kg.